HUBUNGAN FAKTOR LINGKUNGAN FISIK DENGAN KEJADIAN PENYAKIT CHIKUNGUNYA DI DESA TANAH RAJA - Tarigan, Yenni Agustiani (Jurnal Mutiara Kesehatan Masyarakat, 2016)
Chikungunya is a self-limiting disease that caused by chik virus. Chik virus is Alphavirus group in Togaviridae family. This disease is signed with acute fever, pain in articulation especially at knee joint, wrist, finger and toe, as well as spinal column with an eruption of the skin. On Mei 2009, in Tanah Raja occurred Chikungunya outbreaks that attack 165 citizen. This study purpose was to know the characteristic of society and the association of physical environmental factors on Chikungunya disease at Tanah Raja, Sei Rampah District, Serdang Bedagai.It was an observational research using case control design. We used a questionnaire to collect information data from participants. The number of samples were 60 participants that consists of 30 participants in case group and 30 participants in control group. Chisquare test was used to examine the association of environmental factors with Chikungunya disease. The results showed that the highercharacteristicofparticipants based on age is middle-aged and older = 36 people (60%), man = 46 people (76.7%), the education level for primary school = 23 people (38.3%), and occupation as laborer = 55 people (97.7%).Physics environmental factors such as, bad room lighting = 41 houses (68.3%), bad vessel lighting = 49 houses (81.7%), and bad existence of mosquito-larva = 42 houses (70%). In bivariate analysis showed that sex (p = 0.015, OR = 0.192; 95% CI = 0.047-0.782) and existence of mosquito-larva (p = 0.001, OR = 0.111; 95 % CI = 0.028 - 0.447) were involved in Chikungunya outbreaks in Tanah Raja. There was an association of sex and existence of mosquito-larva on Chikungunya outbreaks. Therefore suggested to all of society (participants) to increase activity in destroying nest-mosquito, put abate selection or grow fish to eat the larva or do house fogging to hit mosquito population. Keyword: Chikungunya, Outbreak, Physics environmental factor.